APPLICATION OF FUZZY LOGIC OF THE SUGENO METHOD TO DETERMINE THE AMOUNT OF PRODUCTION OF DRY POTATO SAMBAL - Ayup Panjaitan Wicaksana; Tri Hastono; Mirna Septianingrum Solikhah (CV. Fahr Publishing, 2024)
Home industry has become the primary choice in the entrepreneurial world. One example of a home industry is Putro Prasojo's dried cassava chili paste. In the realm of production, this capability involves the skill of planning or determining the production volume. The goal is to ensure that market demand is met accurately while also considering inventory levels to achieve maximum profit. Several factors are considered in determining the production volume, involving an evaluation of the existing inventory and consideration of the demand levels. Facing these challenges, determining the right production volume to meet consumer demand requires alternatives. Applying the Sugeno Fuzzy Method using the MATLAB toolbox. This research is expected to establish an optimal production design. The Sugeno Fuzzy Logic Method used to determine the production volume of Putro Prasojo's dried cassava chili paste based on inventory and demand data can be an effective decision-making tool for the company. This method provides truth values to the decisions made, with a truth value reaching 82.787%.